Ethnical Barriers Tenaga Kerja Lokal Tambak Garam di Kota Surabaya dalam Perspektif Kualitatif Etnografi - Sahara, Rika; Kristiyanto, Sony (Economie: Jurnal Ilmu Ekonomi, 2020)
This study aims to find out more deeply about obstacles for local labor (ethnic Javanese) as salt farmers in the city of Surabaya. There is an absolute requirement in the use of salt-producing labor in Surabaya City. This research uses qualitative method with ethnography study approach. Data collection technique using indepth interviewing method. The sample used in this research is seven people by using sampling technique snowball sampling that is getting information or data based on recommendation from others who really understand the problem of this research. The result of this research is finding a fact that in the salt production activity in Surabaya City is required to use non-local worker with ethnic Madura on the grounds that only Madurese ethnic workers are willing and able to accept the heavy consequences that have been arranged by the owner of the pond salt in the city of Surabaya. Salt pond owners in the city of Surabaya do not impose barriers to local labor to produce salt, as evidenced by a new innovation by transferring the function of empty land into an artificial salt pond in order to attract local labor.